Experiences of Black African Faculty at American Higher Education Institutions: Issues, Concerns, and Strategies (Comparative & International Education Series, 2021)
International faculty are foreign-born instructors and educational professionals who are primarily employed in the American higher educational system. The number of International faculty in American higher education institutions has been on the rise for over two decades as result of changes in American immigration laws. These faculty members make immense contributions to their campuses via the internationalization of their respective campuses. Like every other sector, there are also challenges that accompany their roles. This chapter highlights the experiences of Black African international faculty in the United States with particular emphasis on their workplace experiences, promotion and tenure, and contributions to their respective institutions. Challenges and concerns faced are also explored along with strategies to mitigate some of the main issues faced by this population.